Neurovisual Assessment in Children with Ataxia Telangiectasia - Iodice, Alessandro; Galli, Jessica; Molinaro, Anna; Franzoni, Alessandra; Micheli, Roberto; Pinelli, Lorenzo; Plebani, Alessandro; Soresina, Annarosa; Fazzi, Elisa (Neuropediatrics, 2018)
Aim Visual impairment is present in almost all patients with ataxia telangiectasia (AT) and, due to their early onset, constitute an important disabling aspect of the syndrome: the quality of vision is limited by dyspraxia and oculomotor abnormal movements. The purpose of this observational study was to describe visual disorders, notably oculomotor impairment, in a sample of children with AT.Methods Fifteen AT patients (mean age 12 years and 4 months) underwent a neurovisual evaluation, particularly focused on oculomotor functions (fixation, smooth pursuit, saccades, and abnormal ocular movements). We compared the visual profile obtained with that described using the International Cooperative Ataxia Rating Scale (ICARS) subscale of oculomotor dysfunction.Results Refractive errors were seen in eight patients and strabismus in three. Major oculomotor findings were fixation abnormalities (6/15), saccadic impairment (15/15), and abnormal smooth pursuit (14/15). Abnormal ocular movements were seen in 13/15 (saccadic intrusion in 8 and nystagmus in 5). Using ICARS scale, 13/15 children presented gaze-evoked nystagmus, 4/15 a clearly saccadic pursuit, and 11/15 dysmetria of saccades.Discussion We propose a clinical neurovisual evaluation, which could be integrated with ICARS scores in the study of oculomotor involvement in AT pediatric patients. We strongly recommend the empowerment of visual functions to slow down progressive global disability of these patients.
Keywords: ataxia telangiectasia; neurovisual disorders; oculomotor dyspraxia; International Cooperative Ataxia Rating Scale